The perspective of the concept of identification in the scope of Spanish and Brazilian Archival Science - Penha, Noemi Andreza da (2021)
The identification came as part of archival science in the mid 80's, as proposed methodological group of archivists to solve the problem of accumulation of documents. In Brazil, the proposed identification made under the National Archives resulted in the publication of manuals and the concept has been incorporated by the Dictionary of Archival Terminology, published in 2005. However, it appears that there is no ordering of the theoretical and methodological aspects that involve the identification in the context of Brazilian archival science. Thus, this paper aims to study the construction of the concept of identification, mapping the methodological initiatives to systematize them in the perspective of the Brazilian Archival Science, producing a picture of the use of terminology identification indicated by the authors studied, contributing to the theoretical construction of archival science in Brazil.